Spin-polarized calculations of structural, electronic and magnetic properties of Half Heusler alloys FeVX (X=Si, Ge, Sn) using Ab-initio method. (15th August 2016) - Sattar, M. Atif; Rashid, Muhammad; Hashmi, M. Raza; Rasool, M. Nasir; Mahmood, Asif; Ahmad, S.A.
Abstract: In this study, density functional theory based ab-initio calculations are utilized to investigate the electronic and magnetic properties of new series of Half Heusler FeVX (where X=Si, Ge, Sn) compounds. We have considered the C1b -type structure of these materials in three atomic configurations, termed as α, β, and γ phases, in order to find the most stable geometric structure. The structural properties of all three phases have been determined and the effect of spin-polarization has been studied. Our calculated electronic properties suggest that the studied materials under study are half-metallic (HM) ferromagnets and stable in the α-phase. We have also employed the modified Becke–Johnson (mBJ) local spin density approximation functional for a better description of the HM response of FeVX materials. We have also shown that the HM nature of FeVX compounds is robust for a wide range of lattice constant, making these materials suitable for spintronic applications.